Analysis of stock liquidity in banking development: Evidence from Bank Jago - Ayunda, Adhelia Shury; Purnamasari, Vidya (Optimum: Jurnal Ekonomi dan Pembangunan, 2025)
This study is based on the development of digital banks that have begun to increase along with the emergence of many digital banks and the increase in the value of digital bank transactions since the Covid-19 pandemic in Indonesia. This study aims to determine the growth pattern of Bank Jago's success which causes several factors to influence stock liquidity, namely company value, stock trading volume and stock trading frequency. The analysis method used is VECM (Vector Error Correction Model), a statistical technique that captures both short-term and long-term dynamics in a system of variables, making it particularly suitable for studying stock liquidity. The data used is monthly data with a time span from January 2020 to December 2023. The results of the VECM estimation test show that the variables of company value, stock trading volume and stock trading frequency have an effect on stock liquidity in the long-run due to the emergence of speculation that digital banks have positive prospects during the Covid-19 pandemic which caused an increase in Bank Jago shares from various aspects and had no effect in the short term due to a decline in investor views and company performance in the period at the end of 2022. The implication of this study can be used to formulate strategies to increase stock liquidity at Bank Jago and can be implemented in other digital banks.